Audience-Based Indicators for News Media Performance: A Conceptual Framework and Findings from Germany - Hasebrink, Uwe (2020)
Many attempts to conceptualize and to assess the performance of media systems or single news media outlets focus on the “supply side” of public communication, operationalized as characteristics of the news content and the form of presentation. These characteristics indicate the potential performance of news media; they are a necessary but not a sufficient condition for media performance. In order to assess the actual performance of news media we need to know what kind of audiences they reach, how they fulfil their users’ news-related interests and needs, and how they contribute to their users’ perceptions of the news environment. In this article, we propose a conceptual framework for the definition of audience-based indicators for news media performance. We apply this framework to data gathered as part of the 2019 Reuters Institute Digital News Survey for Germany. We compare 42 news media, both online and offline, in regard to their reach in different parts of the population, and to their audiences’ interest in news and politics, their trust in media, and their perceptions of the overall performance of German news media. The findings underline that news media performance is a multidimensional concept and that there are different ways in which news media can perform. Furthermore, the particular type of media, technically or organizationally, still matters when it comes to audiences’ expectations and perceived functions.